Interrogating Governments’ Interventions in Communal Clashes: The Erin-Ile/Offa Conflicts in Perspective (Global Journal of Human-Social Science, 2019)
Offa is an ancient town and Headquarter of Offa Local Government Area of Kwara State Nigeria Offa is the second largest town in Kwara State after the state headquarters- Ilorin The town is located in central Nigeria with geographic coordinate of 8 9N 4 4 3E Offa was founded by Olalomi Olofa-gangan a crown prince from Oyo kingdom and a direct descendant of king Oranmiyan in Ile- Ife he founded the town around 1395 AD Olalomi was a renowned hunter reputed for his dexterity as an archer Offa according to oral history in the traditional headquarters of Obolo dialect of the Yoruba speaking people of Kwara and Osun States History has it that Offa town was a satellite of the old Oyo kingdom which paid her tributes to the old Oyo kingdom Subsequent due to the North-West war Yoruba-Fulani war Offa fell out through a defeat from Ilorin which now placed Offa under the authority of Ilorin Some historians revealed that when the war ended in 1887 the town was badly ravaged by the Northern forces as the people and animals in Offa were killed by the Ilorin forces thereby making the inhabitants of Offa to flee further Westward and build other town like Ofatedo Ilofa Oke-Offa in Ibadan among others